2018
DOI: 10.26508/lsa.201800113
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic m6A methylation facilitates mRNA triaging to stress granules

Abstract: m6A modification in the 5′ vicinity of the coding sequence of transcripts provides a selective mechanism for triaging mRNAs to stress granules and is mediated by the YTHDF3 “reader” protein.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
135
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(147 citation statements)
references
References 50 publications
8
135
2
Order By: Relevance
“…2 or edgeR, Table 1) 30,31,[55][56][57] . In the mouse cortex and Huh7 cell data, we found that, similar to RNA-seq data 24,56,58 , the variance in read counts under peaks exceeded their mean, indicative of overdispersion ( Supplementary Fig. 6a).…”
Section: Detection Of Peaks Across Replicates Experiments and Cell mentioning
confidence: 57%
See 2 more Smart Citations
“…2 or edgeR, Table 1) 30,31,[55][56][57] . In the mouse cortex and Huh7 cell data, we found that, similar to RNA-seq data 24,56,58 , the variance in read counts under peaks exceeded their mean, indicative of overdispersion ( Supplementary Fig. 6a).…”
Section: Detection Of Peaks Across Replicates Experiments and Cell mentioning
confidence: 57%
“…have reported changes to m 6 A with heat shock, microRNA expression, transcription factor expression, cancer, oxidative stress, human immunodeficiency virus (HIV) infection, Kaposi's sarcoma herpesvirus (KSHV) infection, and Zika virus infection, including hundreds to thousands of changes in enrichment at specific sites [20][21][22][23][24][25][26][27][28][29] . Statistical approaches to analysis have only recently been published and there have been no comprehensive evaluations of methods to detect changes in m 6 A based on MeRIP-seq data 30,31 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, m 6 A modifications in the 5′‐UTR of ATF4 mRNA (containing uORFs) regulate ribosome scanning and selection of start site under conditions of amino acid starvation. Additionally, a dose‐dependent response to sodium arsenite increases m 6 A signals at THE 5′‐UTR and 5′‐vicinity of CDS of mRNAs, which promotes their targeting to SGs via interaction with YTHDF3 protein . All this suggests that global and alternative translation is modulated by m 6 A modifications within mRNAs.…”
Section: Emerging Topics and Future Perspectivesmentioning
confidence: 96%
“…Additionally, a dose-dependent response to sodium arsenite increases m 6 A signals at THE 5′-UTR and 5′-vicinity of CDS of mRNAs, which promotes their targeting to SGs via interaction with YTHDF3 protein. [120] All this suggests that global and alternative translation is modulated by m 6 A modifications within mRNAs. We agree here that m 6 A (and likely other RNA modifications) broadly contribute to stress response by targeting "housekeeping" transcripts to SGs and stimulating alternative translation of pro-survival transcripts; we also speculate that it provides a dynamic synergy between tRNA pools and modified/unmodified mRNAs to rapidly alter proteome for translational response to stress.…”
Section: Emerging Topics and Future Perspectivesmentioning
confidence: 99%